F2 slope as a Perceptual Cue for the Front–Back Contrast in Standard Southern British English. (September 2017) - Chládková, Kateřina; Hamann, Silke; Williams, Daniel; Hellmuth, Sam
Acoustic studies of several languages indicate that second-formant (F2) slopes in high vowels have opposing directions (independent of consonantal context): front [iː]-like vowels are produced with a rising F2 slope, whereas back [uː]-like vowels are produced with a falling F2 slope. The present study first reports acoustic measurements that confirm this pattern for the English variety of Standard Southern British English (SSBE), where /uː/ has shifted from the back to the front area of the vowel space and is now realized with higher midpoint F2 values than several decades ago. Subsequently, we test whether the direction of F2 slope also serves as a reliable cue to the /iː/-/uː/ contrast in perception. The findings show that F2 slope direction is used as a cue (additional to midpoint formant values) to distinguish /iː/ from /uː/ by both young and older Standard Southern British English listeners: an otherwise ambiguous token is identified as /iː/ if it has a rising F2 slope and as /uː/ if it has a falling F2 slope. Furthermore, our results indicate that listeners generalize their reliance on F2 slope to other contrasts, namely /ɛ/-/ɒ/ and /æ/-/ɒ/, even though F2 slope is not employed to differentiate these vowels in production. This suggests that in Standard Southern British English, a rising F2 seems to be perceptually associated with an abstract feature such as [+front], whereas a falling F2 with an abstract feature such as [-front].